Rhinosporidiosis: A Chronic Tropical Disease in Lateral Pharyngeal Wall - Prasad, Vishnu (J Clin Diagn Res, 2015)
Rhinosporidiosis is a chronic granulomatous disease caused by Rhinosporidium seeberi. It predominantly affects the mucous membranes of the nose and the nasopharynx. Clinically the lesion presents as a pink or red pedunculated polyp in one or both nostrils. Diagnosis can be made by aspiration cytology and examination with May-Grunwald-Giemsa, hematoxylin and eosin, Periodic acid-Schiff and mucicarmine staining. Definitive diagnosis is by histopathology of the specimen. We report a case of Rhinosporidiosis at the lateral pharyngeal wall which is a very rare site for Rhinosporidiosis to occur; was treated by diathermy excision of the mass and cauterization of the base and oral Dapsone to prevent recurrence of the disease.